Case Study : Hasnuri Sdn Bhd / Farahanim Yusnita Razali - Razali, Farahanim Yusnita (2021)
The case study is important to evaluate the company’s background, company’s analysis as well as the company’s problems all alternatives that the management has provided. The methods that used to study the analysis is face-to-face interviews with the management of the company through phone call and review from people already have purchased and taste the products. But here, my case study is individual because we are in PKP. So, I already chose the products in google.Based on the findings during the Google Search, the idea of boutique collection provides ready - made Muslimah clothes such as robes, baju kurung , blouses , skirt, palazzo for woman created by Mohd Hasbullah Awang as a CEO of Hasnuri Sdn Bhd. The Hasnuri was started in March 2014. During an interview, Hasbullah Awang said every product made by Hasnuri boutique is limited edition , so to maintain the exclusive features of the product , while making it affordably price , to suit every layer of society.